Effect of plant growth regulators on fruit growth and quality development of syzygium samarangense (water apple/wax apple) / Adel Mohammed H. Al-Saif - Al-Saif, Adel Mohammed H. (2011)
The present study was conducted to investigate the effects of Gibberellic Acid (GA3), Naphthalene Acetic Acid (NAA) and N-2-chloro-4-pyridyl-N-phenylurea (CPPU) on the growth and quality development of water apple/ wax apple (Syzygium samarangense). GA3 at the concentrations of 0 (water control) 30, 60 and 90 ppm was used in experiment 1. NAA at the concentrations of 0 (water control), 6, 12 and 18 ppm was used in experiment 2. CPPU at the concentrations of 0 (water control) 10, 15 and 20 ppm was used in experiment 3. The swabbing technique of hormone application was used for all plant growth regulator applications in the three experiments. The growth regulators at different concentration levels (GA3, NAA and CPPU) were applied once a week starting from bud formation stage to flower opening stage (blooming), of twelve year old trees. In the GA3 experiments, it was observed that application of GA3 (30, 60 and 90 ppm) increased fruit length and diameter. Fruit length and diameter proved to be highest in GA3 at 60 ppm (60 mg/l). Furthermore, it increased the rate of fruit growth and maturity (represented by color) development in addition to increasing fruit number, weight and yield. Premature fruit drop was observed to have declined. With regard to fruit quality, the application of GA3 at 60 ppm increased the TSS , inverted sugar, fructose and total flavonoid content in wax apple. In addition, anthocyanin, potassium (K+) and total phenol content were higher in GA3 treated fruit than control fruit.